The Effect of Health Education Using Stunting Smart Cards Toward Knowledge and Stress on Pregnant Women for Stunting Prevention - Sukarma, Yolanda; Putri, Dewi Eka; Yaslina, Yaslina (GLOBAL HEALTH SCIENCE GROUP, 2024)
Pregnant women are subject to various risk factors that render them physically and psychologically vulnerable, increasing the risk of stunting in their babies. Insufficient knowledge and mental health issues during pregnancy elevate the risk of stunting by 10.2 times. These factors can lead to delayed fetal development, disrupt nutrient metabolism, and negatively affect health, ultimately contributing to stunting. One potential intervention to enhance pregnant women's knowledge and manage stress involves the use of targeted health education through Stunting Smart Cards. This study aimed to assess the effect of health education using Stunting Smart Cards on the knowledge and stress levels of pregnant women. Quantitative study, quasi-experimental pretest-posttest design with control groups. The study included 46 pregnant women selected through purposive sampling, with 23 participants in each of the intervention and control groups. The study was conducted at Seberang Padang and Ikur Koto Health Centers. Data analysis was carried out using Paired t-tests and Wilcoxon tests. The mean knowledge score in the intervention group significantly increased from 7.08 (low) to 9.82 (high) after the intervention. Concurrently, the mean stress score decreased from 107.73 (severe) to 73.86 (moderate). In contrast, the control group exhibited minimal changes, with knowledge scores increasing slightly from 6.56 to 7.39, and stress levels remaining stable at 107.00 post-intervention. This study found a significant effect of health education using Stunting Smart Cards on improving knowledge and reducing stress in pregnant women as part of stunting prevention efforts in Padang City Health Centers.